Structural characterization of canine mammary tissue by x-ray diffraction. (February 2019) - Fagundes, A.C.F.; Lopes, L.M.; Antoniassi, M.; Sousa, R.S.; Mazzaro, I.; Conceição, A.L.C.
Abstract: The life expectance in canines is increasing due to the improvement in health care. However, some age diseases as mammary cancer are arising and represent about 50% of the cancers diagnosed in females. Nowadays, researches are focusing efforts to identify structural changes into canine mammary tissues due to cancer progression. In this sense, X-ray diffraction is a powerful tool for this purpose. Therefore, this study aims to characterize structurally the normal and cancerous canine mammary tissue by X-ray diffraction. A total of 83 canine mammary samples histopathologically classified as normal, benign and malignant, were used in this study. Using a commercial powder diffractometer, the scattering profiles of each sample were determined. From these scattering profiles, two broad peaks were identified at q = 13.9 nm −1 and q = 19.8 nm −1 . The values of intensity of both peaks and the ratio of these intensities were obtained. Significant difference between all pairs of group of investigated tissues was observed. Finally, the strong similarity between normal and pathological human and canine tissue found in this study corroborates to comparative oncology between humans and canines. Highlights: X-ray diffraction is used to check the structural rearrangement in canine mammary tumor. The scattering profiles distinguish between health and tumoral canine mammary tissue. A strong similarity between human and canine mammary tissue was found.